A study into the awareness and acceptance of utilizing vine branches in the micro-region of Gyöngyös - Gonda, Cecília (Applied Studies in Agribusiness and Commerce, 2013)
Every year, a significant amount of renewable dendromass is generated in Hungary. Various possibilities have been recognised by today that are not widespread yet. The greatest obstacle is frequently derived from the lack of the farmers’ knowledge as without having the required knowledge obtained they can become distrustful or adequate efficiency will not be achieved during utilisation. In order to improve the rate of utilisation, targeted information methodologies should be applied that comply with the farmers’ knowledge. In this present study, the awareness and acceptance of vine-growers from the Micro-region of Gyöngyös related to the use of vine branches will be analysed based on the results of a questionnaire survey. The survey was conducted in accordance with the number of wine-community members in personal interviews. The questionnaire contained questions about the farm, the use of vine branches as well as about the farmers. Based on the results, information was obtained on the reasons for the use of by-products not being wide-spread among farmers as well as on the sources of information obtained. For the fragmented farms which are typical here it is important to know whether by-products are not utilised as it is not how they can be used or whether the vineyard is cultivated by others therefore the farmer lacks machinery. The level of acceptance was also studied by asking a question on the possible offer of the by-products for greater-scale site. Our intention is to assist the generally badly off farmers to use the annually generated by-products in a reasonable way. This can be realized by various ways of providing information. By applying the results of the survey, adequate methods and knowledge can be provided for farmers.